Photocatalysis-mediated drug-free sustainable cancer therapy using nanocatalyst - Bin Zhao (Nature Portfolio, 2021)
Nanoparticles have been used to reduce the toxicity associated with chemotherapeutic agents. Here, the authors report a Z-scheme SnS1.68-WO2.41 nanocatalyst for photocatalytic generation of oxidative holes and hydrogen molecules for drug-free therapeutic strategy.